EFEKTIVITAS PENERAPAN SANKSI ADMINISTRATIF PELANGGARAN LALU LINTAS DALAM MENINGKATKAN KESADARAN MASYARAKAT DI KABUPATEN NGAWI - Zahra, Meita Fadhilah; Sidarta, Dudik Djaja; Paramitha, Vallencia Nandya (Gapenas Publisher, 2025)
This thesis is entitled ‘The Effectiveness of Administrative Sanctions for Traffic Violations in Raising Public Awareness in Ngawi Regency’. The high number of traffic violations, despite increased enforcement by the authorities, with 6,395 fines and 26,714 warnings recorded in 2024, indicates a low level of public legal awareness. This problem raises questions about the extent to which administrative sanctions can have a deterrent effect and encourage legal awareness. The purpose of this study is to analyse the implementation of administrative sanctions for traffic violations in Ngawi Regency and assess their effectiveness in shaping public legal awareness. This study uses a normative juridical approach supported by field data through interviews, observations, and documentation from the Ngawi Police Traffic Unit, and is analysed using Satjipto Rahardjo's progressive legal theory, which emphasises the need for a humanistic and participatory legal approach so that sanctions are not only repressive but also educational